Java EE and HTML5 enterprise application development - Brock, John (McGraw-Hill Education, 2014)
Build and distribute business Web applications that target both desktop and mobile devices. Cowritten by Java EE and NetBeans IDE experts, this book fully explains cutting-edge, highly responsive design tools and strategies. Find out how to navigate NetBeans IDE, construct HTML5 programs, employ JavaScript APIs, integrate CSS and WebSockets, and handle security. This Oracle Press guide also offers practical coverage of SaaS, MVVM, and RESTful concepts. Topics include: exploring HTML5 and Java EE 7 features; using NetBeans IDE editors, templates, and code generators; implementing MVVM functionality with Knockout.js; mapping database objects using Java Persistence API; configuring, managing, and invoking RESTful Web Services; maximizing messaging efficiency through WebSockets; accepting and processing HTML5 Server-Sent Events streams; and employing Syntactically Awesome Stylesheets, CSS3, and Sassy CSS.
Includes bibliographical references and index. - Print version record
Keywords: Application software -- Development; Java (Computer program language); HTML (Document markup language); Logiciels d'application; Développement; Java (Langage de programmation); HTML (Langage de balisage); HTML; Application software; Development